Productivity of clusterbean (Cyamopsis tetragonoloba) and sesame (Sesamum indicum) intercropping system under different row ratio and nutrient management in arid region - Meena, Samrath Lal; Shamsudheen, M; Dayal, Devi (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during rainy (kharif) seasons of 2005 to 2007 at Bhuj to find out possibility of increasing production of clusterbean (Cyamopsis tetragonoloba L. Taub.) and sesame (Sesamum indicum L.) through spatial arrangement and nutrient management. The soil was gravelly-sandy loam with shallow depth (21 cm) and pH 8.7. The clusterbean equivalent yield (919 kg/ha), net returns (Rs 7 440/ha), benefit: cost ratio (1.80) and sustainable yield index (0.74) were higher with clusterbean + sesame (2:1) intercropping system over the sole crop of clusterbean (710 kg/ha, Rs 5 945/ha, 1.68 and 0.71 respectively). Irrespective of cropping systems, application of 20 kg N/ha + 5 tonnes farmyard manure/ha recorded significantly higher clusterbean-equivalent yield (1 036 kg/ha), net return (Rs 1 1171/ha), benefit: cost ratio (2.14) and sustainable yield index (0.80) over 40 kg N/ha alone and absolute control. The row ratio of 2:1 in clusterbean + sesame intercropping fertilized with 20 kg N + 5 tonnes farmyard manure/ha may be recommended to get more economic benefit and sustained yield in arid region.